2013
DOI: 10.3390/en6084207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Driven by Siphon Flow: Parallel Experiments Using the Anaerobic Reactors with Different Mixing Modes

Abstract: Abstract:The effect of mixing by siphon flow on anaerobic digestion, sludge distribution and microbial community were examined in parallel experiments using a siphon-mixed reactor (SMR), an unmixed reactor (UMR) and a continuously mixed reactor (CMR). The SMR performed well without the accumulation of fatty acids under COD loading rates varying from 3 to 18 kg/m 3 /day, while the UMR was totally acidified when the loading rate increased to 10 kg/m 3 /day. The methane yield of the SMR was at least 10% higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is well known that a good stirring/mixing of the digester's content is of high importance to evenly spread fresh feedstock material within the digester, to ensure a close contact between the substrates (i.e., the nutrients supplied with the feedstocks) and the degrading microorganisms, to facilitate the removal of end products of metabolism and the upflow of gas bubbles, as well as to achieve even temperature conditions across the digester [33,59,60].…”
Section: Nutrient Distributionmentioning
confidence: 99%
“…It is well known that a good stirring/mixing of the digester's content is of high importance to evenly spread fresh feedstock material within the digester, to ensure a close contact between the substrates (i.e., the nutrients supplied with the feedstocks) and the degrading microorganisms, to facilitate the removal of end products of metabolism and the upflow of gas bubbles, as well as to achieve even temperature conditions across the digester [33,59,60].…”
Section: Nutrient Distributionmentioning
confidence: 99%
“…As Table 2 shows, P is especially limited. The PO4 3− concentration was low as in most cases 1-5 mg-phosphorus (P)/L and even NH4 + concentration was usually below 1000 mg-N/L, while those in the food waste-digestion were about 1500-4000 mg-N/L and 60-200 mg-P/L in the previous study [24]. Furthermore, low concentration of micronutrients such as Fe, Co could contribute to limit activity of microbial consortia.…”
Section: Characteristics Of Organic Compounds Degradationmentioning
confidence: 65%
“…These data supports that hydrolysis was generally limited, resulting in no significant accumulation of the intermediates present, and methanogenesis rate was reduced when the HRT was 15 days. The hydrolysis rate constant (kh) of the semi-continuous experiment was calculated using the acid-phase model and was compared with the kh values obtained from our previous studies dealing with conventional digestion substrates [24,29]. All three substrates contained around 100 g/L TS and these were digested in a semi-continuous mode using mesophilic continuously mixed reactors.…”
Section: Rate Limitingmentioning
confidence: 99%
“…Previous studies stated that the abundance of the methanogenesis showed a significant increase at low mixing frequency (50–60 rpm) or minimal rather than high [ 35 ]. On the other hand, the SDSAR with siphon-mixed model had higher MY compared with other anaerobic digesters with unmixed or continuously mixed models in the FW treatment [ 36 ]. However, the experimental results in present study showed no significant correlations between MY and siphon-mixing frequency at various lipid concentrations.…”
Section: Resultsmentioning
confidence: 99%